Influence of the preparation process on the chemical composition and nutritional value of canned purée of kabuli and Apulian black chickpeas. Issue 3 (March 2019) - Summo, Carmine; De Angelis, Davide; Rochette, Isabelle; Mouquet-Rivier, Claire; Pasqualone, Antonella
Abstract: Chickpeas are classified into two main commercial seed types: desi, and kabuli . Furthermore, the Apulian black is another chickpea type, less common, which has peculiar phenotypic and genetic features and is the object of an increasing attention by geneticists to avoid the risk of genetic erosion. A strategy to increase the consumption of pulses consists in proposing ready-to-eat gastronomic preparations which, however, must keep their natural features and nutritional value as intact as possible. In this paper the influence of the preparation process on the chemical composition and nutritional value of ready-to-eat canned purée of Apulian black chickpeas has been evaluated, in comparison with purée of kabuli chickpeas. Total dietary fiber content was high enough to consider the kabuli chickpea purée as "source of fiber", and the black chickpea purée as "high fiber", in accordance with the current European Regulation on nutrition claims. Along the preparation process, an increase in lipid content was observed. Protein content, instead, showed a different behaviour, i.e. increased in Apulian black chickpea purée and remained constant in kabuli chickpea purée. The preparation process strongly influenced fatty acid composition. In particular, unsaturated fatty acids decreased in both Apulian black and kabuli chickpea purées, whereas saturated fatty acids significantly increased during processing. Apulian black chickpeas are particularly rich of bioactive compounds, but the preparation process of purée caused a strong decrease of total carotenoids, anthocyanins and phenolic compounds. However, even after processing, this purée could still be a good source of bioactive compounds. All these features make canned purée of chickpeas a healthy ready-to-eat food, which is at the same time rich in fiber and bioactive compounds, able to fulfill the time-saving needs of modern lifestyle. These findings could promote a greater use of Apulian black chickpeas and contribute to reduce the risk of genetic erosion.